2013
DOI: 10.1007/s10597-013-9635-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship Between Treatment Satisfaction, Perceived Improvements in Functioning and Well-Being and Gambling Harm Reduction Among Clients of Pathological Gambling Treatment Programs

Abstract: The objective of this study was to evaluate the relationship between treatment service quality, perceived improvement in social, functional, and material well-being and reduction in gambling behaviors among clients of Nevada state-funded pathological gambling treatment programs. Utilizing survey data from 361 clients from 2009 to 2010, analyses revealed that client satisfaction with treatment services is positively associated with perceived improvements in social, functional, and material well-being, abstinenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 71 publications
(102 reference statements)
1
10
0
Order By: Relevance
“…This, interestingly coincided with a study by Monnat, Bernhard, Abarbanel, John & Kalina 10 evaluating the relationship between treatment service quality, perceived improvement in social, functional, and material well-being and reduction in gambling behaviors among clients of Nevada statefunded pathological gambling treatment programs. The analyses revealed that client satisfaction with treatment services is positively associated with perceived improvements in social, functional, and material well-being, abstinence from gambling, reduction in gambling thoughts and reduction in problems associated with gambling, What stands out in the 2014 study in terms of the predictors of good treatment outcome included a later exposure to gambling (after the age of 21) and being a strategic gambler.…”
Section: Predictors Of Treatment Outcomesupporting
confidence: 70%
“…This, interestingly coincided with a study by Monnat, Bernhard, Abarbanel, John & Kalina 10 evaluating the relationship between treatment service quality, perceived improvement in social, functional, and material well-being and reduction in gambling behaviors among clients of Nevada statefunded pathological gambling treatment programs. The analyses revealed that client satisfaction with treatment services is positively associated with perceived improvements in social, functional, and material well-being, abstinence from gambling, reduction in gambling thoughts and reduction in problems associated with gambling, What stands out in the 2014 study in terms of the predictors of good treatment outcome included a later exposure to gambling (after the age of 21) and being a strategic gambler.…”
Section: Predictors Of Treatment Outcomesupporting
confidence: 70%
“…These enhancements also pertained to the psychopathology of gambling, such as urge/craving ( Abbott et al., 2017 ; Giordano et al., 2022 ; Hawker et al., 2021 ; Humphrey et al., 2020 ; Oei et al., 2018 ), desire to gamble ( Echeburúa et al., 1996 , 2000 ; Ladouceur et al., 2001 , 2003 ; Sylvain et al., 1997 ), gambling-related cognitive distortions ( Abbott et al., 2017 ; Giordano et al., 2022 ; Oei et al., 2018 ; Rossini-Dib et al., 2015 ), and time spent thinking about gambling ( Echeburúa et al., 1996 , 2000 ; Monnat, Bernhard, Abarbanel, St John, & Kalina, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, some studies evaluated readiness, willingness, and ability to change ( Humphrey et al., 2020 ; Wulfert et al., 2006 ), as well as current goals at follow-up and self-rated goal achievement ( Abbott et al., 2017 ; Hodgins, Cunningham, Murray, & Hagopian, 2019 ; Stea et al., 2015 ). One study examined decreases in gambling-related problems and gambling harm reduction ( Monnat et al., 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…3 Given the breadth of available treatment methods and the simultaneous observation that a minority of people seek help, it is necessary to identify which methods people with PG tend to seek out as well as their perceived helpfulness, as this contributes to treatment satisfaction, which has been positively associated with social, functional, and material well-being. 4 Some studies-conducted in Australia, 5 New Zealand, 6 and Ontario (Canada) 7 -have looked at the uptake of various strategies to limit or reduce gambling. Although, the number of participants who reported seeking formal or informal treatment in these studies was relatively small (ranging from 12 to 68), results consistently show that people tend to favor informal sources of help and self-help materials.…”
Section: Introductionmentioning
confidence: 99%
“…These can be in the form of self-guided treatment material, individual counseling with a health professional, group therapy (including Gamblers Anonymous), or residential (inpatient) treatment; even pharmacological treatments have been trialed to help people with PG 3 . Given the breadth of available treatment methods and the simultaneous observation that a minority of people seek help, it is necessary to identify which methods people with PG tend to seek out as well as their perceived helpfulness, as this contributes to treatment satisfaction, which has been positively associated with social, functional, and material well-being 4 …”
Section: Introductionmentioning
confidence: 99%